Alterations of neuromuscular junctions in Duchenne muscular dystrophy. (15th October 2020) - Lovering, Richard M.; Iyer, Shama R.; Edwards, Benjamin; Davies, Kay E.
Graphical abstract: Highlights: Duchenne muscular dystrophy (DMD), the most common form of muscular dystrophy, is caused by the lack of dystrophin, a protein encoded by the DMD gene. The neuromuscular junction (NMJ) is not a fixed, permanent structure, but instead shows plasticity in response to injury, exercise, and aging. NMJs in the mdx mouse model of DMD show aberrant changes in both pre- and post-synaptic NMJ structure, which could influence neuromuscular transmission. The hypothesis that the NMJ contributes to functional deficits in DMD represents a paradigm shift from more prevalent myo-centric perspectives. Abstract: The focus of this review is on Duchenne muscular dystrophy (DMD), which is caused by the absence of the protein dystrophin and is characterized as a neuromuscular disease in which muscle weakness, increased susceptibility to muscle injury, and inadequate repair appear to underlie the pathology. Considerable attention has been dedicated to studying muscle fiber damage, but data show that both human patients and animal models for DMD present with fragmented neuromuscular junction (NMJ) morphology. In addition to pre- and post-synaptic abnormalities, studies indicate increased susceptibility of the NMJ to contraction-induced injury, with corresponding functional changes in neuromuscular transmission and nerve-evoked electromyographic activity. Such findings suggest that alterations in the NMJ of dystrophic muscle may play a role in muscle weakness via impairment of neuromuscular transmission. Further work is needed to fully understand the role of the NMJ in the weakness, susceptibility to injury, and progressive wasting associated with DMD.